An increased bone mineral density is an adverse prognostic factor in patients with systemic mastocytosis - Riffel, Philipp; Schwaab, Juliana; Lutz, Christopher; Naumann, Nicole; Metzgeroth, Georgia; Fabarius, Alice; Schönberg, Stefan; Hofmann, Wolf-Karsten; Valent, Peter; Reiter, Andreas; Jawhar, Mohamad (Journal of cancer research and clinical oncology, 2020)
Systemic mastocytosis (SM) is characterized by the expansion of clonal mast cells that infiltrate various organ systems. The extent of organ infiltration and subsequent organ damage distinguishes between indolent SM (ISM) defined by a nearly normal life expectancy and advanced SM (AdvSM) defined by poor prognosis. In ISM, measurement of the bone mineral density (BMD) frequently reveals osteoporosis. In contrast, the clinical implication of an increased BMD and osteosclerosis remains unclear.